A DELEUZIAN INCURSION INTO KANTIAN CRITICISM. ABOUT THE DOCTRINE OF THE FACULTIES FROM THE PERSPECTIVE OF THEIR INTEREST - MARTA, Claudia (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
A Deleuzian incursion into Kantian Criticism. About the Doctrine of the Faculties from the Perspective of their Interest. Deleuze describes the doctrine of the faculties as a complete system of permutations. These faculties are analyzed in part according to their own interest: speculative or practical. Each faculty has a superior form through which it is realized. Deleuze’s question is to what extent a faculty becomes able to achieve its own interest and bear the legislative burden for another. Reflective judgment generally makes it possible to move from the faculty of knowledge to that of desire, from speculative to practical. These are also questions concerning the free agreement of our faculties with the contingency of Nature’s own accord with them.